The spider genus Patrera Simon (Araneae: Dionycha, Anyphaeninae) in the Atlantic Forest biome, with the description of one new species from Brazil - Oliveira, Luiz Fernando M.; Brescovit, Antonio D. (Zootaxa, 2021)
The species of Patrera Simon, 1903 from Brazilian Atlantic Forest biome are revised. With more than 2715 specimens examined, nine species were found and, of these, only one new species is described, Patrera teresopolis n. sp. from state of Rio de Janeiro. The other valid names were described by a single author: Patrera procera (Keyserling, 1891), P. longipes (Keyserling, 1891), P. virgata (Keyserling, 1891), P. cita (Keyserling, 1891), P. tensa (Keyserling, 1891), n. comb., P. opertanea (Keyserling, 1891), n. comb., P. concolor (Keyserling, 1891), n. comb. and P. recentissima (Keyserling, 1891), n. comb. (Later four here transferred from Teudis O. Pickard-Cambridge, 1896) and P. pellucida (Keyserling, 1891), n. comb. (here transferred from Sillus F.O. Pickard-Cambridge, 1900). The males of Patrera opertanea, P. pellucida and P. recentissima are described for the first time. The species Teudis itatiayae Mello-Leitão, 1915 and Sillus delicatus Mello-Leitão, 1922 are synonymized with P. longipes; Osoriella pallidoemanu Mello-Leitão, 1926 is synonymized with P. concolor. All species are described, illustrated and mapped. The known distribution of Patrera procera and P. longipes is expanded to Argentina and that of Patrera procera to Paraguay.